Program Kampus Mengajar Sebagai Usaha Peningkatan Adaptasi Teknologi untuk Siswa di SMP Nathania Palangka Raya - Rahmat, Muhammad Hudan; Qalby, Luthfia; Akzy, Rhaja Sukma; Nasution, Villatulia Nur'safitri; Haloho, Yesika Kristin; Wardani, Muhammad; Sukardi, Sukardi (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Kampus Mengajar Program is an initiative of Merdeka Belajar Kampus Merdeka that provides opportunities for students to participate in teaching assistance and support the learning process in Junior High Schools located in various villages and cities. One of these schools is SMP Nathania Palangka Raya. In this program, students are tasked with supporting teaching activities and helping students adapt to technology. Additionally, they are responsible for improving students' morals as well as motivating and fostering their interest in learning. This program aims to enhance students' social awareness of their surroundings, develop critical thinking skills in collaboration with teachers and students from various fields of study to solve problems, as well as expand their knowledge, build character, and refine their soft skills. During this activity, a participatory approach is applied, where students interact directly with the pupils to understand the needs and challenges they face. The program employs an interactive and practical learning model to ensure that students can apply the knowledge they have gained. The results of the service show a significant improvement in students' ability to use technology. Students became more confident and actively participated in learning activities. The program also successfully raised students' social awareness about the importance of their contributions to society. This program has achieved its objectives and made a positive impact on both students and schools.